THE LEGAL AND REGULATORY FRAMEWORK FOR MURABAHA - Mukhitdinova Muyassar Ziyaviddinovna (American Journals, 2023)
The legal and regulatory framework for Murabaha plays a crucial role in ensuring the compliance and effectiveness of this Islamic finance mechanism. Murabaha, also known as cost-plus financing, is a common transaction structure used in Islamic finance. It involves the sale of a commodity by a bank to a customer at an agreed markup price, which includes the bank's cost and profit margin. The legal and regulatory framework for Murabaha is designed to ensure that the transaction adheres to Sharia principles and guidelines.This article examines the use of murabaha in Islamic finance. It discusses the advantages and disadvantages of murabaha, and it provides an overview of the different types of murabaha contracts. The article also discusses the legal and regulatory framework for murabaha in different jurisdictions. The article concludes that murabaha is a complex but versatile financing structure that can be used to finance a variety of assets. Murabaha can be a useful tool for businesses and individuals who want to finance assets without having to pay interest. However, it is important to understand the risks and limitations of murabaha before using it.
Keywords: Murabaha, Islamic finance, cost-plus financing, Sharia law, interest-free financing